Recruiting Minorities What Explains Recent Trends in the Army and Navy? - Asch, Beth J. (RAND Corporation, 2009)
Since 2000, black representation among high-quality recruits in the Army has decreased, while Hispanic representation has increased; in the Navy, black representation has remained stable and Hispanic representation has increased. The authors identify factors that explain these trends and consider which policies are likely to be most effective in increasing high-quality enlistments among black, Hispanic, and white youth.